COGNITIVE INDEPENDENCE OF STUDENTS: ESSENCE, MAIN CHARACTERISTICS, STRUCTURE - S.V. Mikhno (Academy of Cognitive and Natural Sciences, 2008)
The article is devoted to further defining of cognitive student's independence more exactly, to the determination ofitsdwracteristics and structure